Influence of Psycho-Demographic Variables on Psychological Well-Being of Undergraduates of Obafemi Awolowo University, Ile-Ife, Osun State - Adeniyi, W. O.; Onadiji, O. (European Scientific Journal, ESJ, 2016)
The study investigated the influence of emotional intelligence on psychological well being of undergraduates as well as determined influence of demographic variables on psychological well being of undergraduates. The study adopted a descriptive survey design. The sample consisted of 480 undergraduates selected from six selected faculties out of the thirteen Faculties in Obafemi Awolowo University, Ile-Ife, using convenience sampling technique. Two adapted instruments titled “Ryff’s Scale of Psychological Well-Being (RSP)” and “Questionnaire on Students’ Emotional Intelligence (QSEI)” were used to collect information from the students. The reliability tests of the instruments used were Spearman Brown Coefficients and Spearman Brown Split-half reliability tests for RSP yielded results of 0.81 and 0.90 while that, of QSEI had 0.85 and 0.80. Descriptive statistics and chi-square statistics were employed to analyse the data. The results showed that 95% of the undergraduates had high level of psychological well being. There was a significant influence of levels of emotional intelligence on psychological well being of undergraduates (χ2 = 0. 577 at p < 0.05). Furthermore, the results showed a significant influence of each of sex (χ2 = 0. 786; p < 0.05) and place of residence (χ2 = 0.624 at p = < 0.05) on psychological well being of undergraduates. However, there was no significant influence of age range on psychological well being of undergraduates (χ2 = 0. 365; p > 0.05). It was concluded that most undergraduates possessed high level of emotional intelligence and that had predisposed to high psychological well being.